Genome-Wide Identification and Function of Aquaporin Genes During Dormancy and Sprouting Periods of Kernel-Using Apricot (Prunus armeniaca L.) - Li, Shaofeng; Wang, Lin; Zhang, Yaoxiang; Zhu, Gaopu; Zhu, Xuchun; Xia, Yongxiu; Li, Jianbo; Gao, Xu; Wang, Shaoli; Zhang, Jianhui; Wuyun, Ta-na; Mo, Wenjuan (Frontiers in Plant Science, 2021)
Aquaporins (AQPs) are essential channel proteins that play a major role in plant growth and development, regulate plant water homeostasis, and transport uncharged solutes across biological membranes. In this study, 33 AQP genes were systematically identified from the kernel-using apricot (Prunus armeniaca L.) genome and divided into five subfamilies based on phylogenetic analyses. Gene structure and conserved functional motif analyses indicated that the PaAQPs exhibit a conserved exon-intron pattern and that conserved motifs are present within members of each subfamily. Physiological mechanism prediction based on the aromatic/arginine selectivity filter, Froger’s positions, and three-dimensional (3D) protein model construction revealed marked differences in substrate specificity between the members of the five subfamilies of PaAQPs. Promoter analysis of the PaAQP genes for conserved regulatory elements suggested a greater abundance of cis-elements involved in light, hormone, and stress responses, which may reflect the differences in expression patterns of PaAQPs and their various functions associated with plant development and abiotic stress responses. Gene expression patterns of PaAQPs showed that PaPIP1-3, PaPIP2-1, and PaTIP1-1 were highly expressed in flower buds during the dormancy and sprouting stages of P. armeniaca. A PaAQP coexpression network showed that PaAQPs were coexpressed with 14 cold resistance genes and with 16 cold stress-associated genes. The expression pattern of 70% of the PaAQPs coexpressed with cold stress resistance genes was consistent with the four periods of flower buds of P. armeniaca. Detection of the transient expression of GFP-tagged PaPIP1-1, PaPIP2-3, PaSIP1-3, PaXIP1-2, PaNIP6-1, and PaTIP1-1 revealed that the fusion proteins localized to the plasma membrane. Predictions of an A. thaliana ortholog-based protein–protein interaction network indicated that PaAQP proteins had complex relationships with the cold tolerance pathway, PaNIP6-1 could interact with WRKY6, PaTIP1-1 could interact with TSPO, and PaPIP2-1 could interact with ATHATPLC1G. Interestingly, overexpression of PaPIP1-3 and PaTIP1-1 increased the cold tolerance of and protein accumulation in yeast. Compared with wild-type plants, PaPIP1-3- and PaTIP1-1-overexpressing (OE) Arabidopsis plants exhibited greater tolerance to cold stress, as evidenced by better growth, greater antioxidative enzyme activities, and greater expression of cold-response genes.